Assessment of the Strengths, Weaknesses, and Gap-Fix Needs of Healthcare Infrastructure in Sierra Leone - Kamara, Yahya Labay; Moiwo, Juana Paul; Vandi, Ahmed; Kawa, Yahaya Kudush (European Journal of Applied Sciences, 2025)
Healthcare in Sierra Leone has faced significant challenges due to historical instability, economic constraints, and disease outbreaks such as the Ebola epidemic. Despite policy reforms like the Free Healthcare Initiative (FHCI) and post-Ebola recovery efforts, systemic weaknesses persist in infrastructure, workforce capacity, and financing, hindering progress toward Universal Health Coverage (UHC). This study assesses the strengths and weaknesses of healthcare infrastructure in Sierra Leone, evaluates the impacts of key interventions, and proposes sustainable strategies for improvement. A mixed-methods approach was used, combining quantitative data analysis from national and international health reports, a systematic literature review (following PRISMA guidelines), and comparative policy analysis. Data sources included the Sierra Leone Ministry of Health, World Health Organization, World Bank, and peer-reviewed studies. The key strengths of healthcare system in Sierra Leone include the success of the FHCI in improving maternal and child health outcomes and the role of community health workers (CHWs) in expanding rural healthcare access. However, critical weaknesses persist, such as severe workforce shortages (0.2 doctors per 10,000 people), inadequate infrastructure (40% of healthcare facilities lack reliable electricity), and heavy reliance on volatile donor funding (60% of health expenditures). Urban-rural disparities remain high, with rural areas experiencing higher maternal mortality and lower vaccination coverage. To strengthen healthcare infrastructure, Sierra Leone must expand medical training, incentivize rural workforce retention, invest in infrastructure through public-private partnerships, and increase domestic health financing. Leveraging technology (e.g., telemedicine) and decentralizing services are also vital. Sustainable progress requires multi-sectoral collaboration, government commitment, and international support to achieve equitable and resilient healthcare delivery.